PENGARUH LIKUIDITAS, OPERATING CAPACITY, UKURAN PERUSAHAAN DANPERTUMBUHAN PENJUALAN TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2016-2017) - Widhy Setyowati; Nadya Ratna Nanda Sari (Magister Manajemen STIE Bank BPD Jateng, 2019)
Financial distress is a phase of decline in financial condition that occurred before the onset of bankruptcy. This study aims to examine the effect of liquidity, leverage, operating capacity, sales growth and firm size of financial distress. This research was conducted at the companies listed on the stock exchange in 2016-2017. The samples used were as many as 108 company observations selected using purposive sampling method. Data collection was done by using the documentation obtained from bei website. The analysis technique used is logistic regression that is helped by e-views 9 program. The results of the analysis of this study indicate that the liquidity, the operating capacity, sales growth and firm size ratios are able to affects the financial distress of manufacturing company with negative direction.